Uji Analgetik Kombinasi Ekstrak Daun Pepaya (Carica papaya L.) dan Daun Kelor (Moringa oleifera L.) pada Mencit Putih (Mus musculus) dengan Uji Geliat - Fahamsya, Arifina; Istriningsih, Endang; Karang, Ananda Kukuh Adi (Department of Pharmacy, Bumigora University, 2025)
Ethnomedicinal plants that have been proven as analgesics are moringa leaves (Moringa oleifera L.) and papaya leaves (Carica papaya L.). The purpose of this study is to determine the analgesic activity of a combination of papaya and moringa leaf extracts. Analgesic testing used the writhing method. A total of 25 mice were grouped into 5 treatment groups, namely negative control (CMC Na 1%), positive control (mefenamic acid 500mg/70kgBW), group I (moringa leaf extract 400mg/kgBW), group II (papaya leaf extract 600mg/kgBW), and group III (combination of moringa leaf extract 200mg/kgBW and papaya leaf extract 300mg/kgBW). The results of the study were obtained using the formula for calculating the percentage of analgesic power and tested using the Post Hoc test and the Least Significant Difference (LSD) test. Based on the analysis, a significant difference was obtained between the treatment group and the negative control. The highest percentage of analgesic effect was obtained from group III, the combination of moringa leaf extract and papaya leaf extract at 56.4%. This result is equivalent to the positive control, with the administration of mefenamic acid.